2019
DOI: 10.1264/jsme2.me18101
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Soil Bacterial Community Compositions in Paddy Fields under Organic and Conventional Farming Conditions

Abstract: Soil bacterial community compositions and temporal changes in organic paddy fields were elucidated using a 16S rRNA gene amplicon sequencing analysis with a high-throughput next generation sequencer. At transplanting, bacterial community compositions in organic and conventional paddy fields were mostly similar despite differences in field management. The bacterial community composition in organic fields differed from that under conventional management during the rice growth period, possibly as a result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Altogether, these observations suggest that rice cultivation and associated treatments, such as fertilization, encourage the proliferation of certain species, which are uniquely adapted and functionally relevant in mineralizing nutrients in the rice-cultivated soil environment compared to the fallow soils and to the 5mR soils, which were not actively managed for the short five months off-season duration. Our observations of fluctuating bacterial species richness and diversity in fields with different rice cultivation status or time points is similar to findings from studies investigating bacterial communities in rice agroecosystem during rice plant developmental stages [110,111], under different farming conditions [112] and for wild and cultivated rice cultivars [113].…”
Section: Discussionsupporting
confidence: 87%
“…Altogether, these observations suggest that rice cultivation and associated treatments, such as fertilization, encourage the proliferation of certain species, which are uniquely adapted and functionally relevant in mineralizing nutrients in the rice-cultivated soil environment compared to the fallow soils and to the 5mR soils, which were not actively managed for the short five months off-season duration. Our observations of fluctuating bacterial species richness and diversity in fields with different rice cultivation status or time points is similar to findings from studies investigating bacterial communities in rice agroecosystem during rice plant developmental stages [110,111], under different farming conditions [112] and for wild and cultivated rice cultivars [113].…”
Section: Discussionsupporting
confidence: 87%
“…A meta-analysis and meta-regression confirmed that organic farming also enhanced soil microbial abundance and activity [25]. In addition, the soil bacterial community compositions were different in paddy fields under organic and conventional farming conditions [26]. In short, the diversity of soil microbial communities (bacterial communities) is complex and different s in various agricultural ecosystem.…”
Section: Introductionmentioning
confidence: 79%
“…Little is known about the root microbial community associated with nature farming and its plant growth-promoting potential under low-input conditions, and no study has been performed on the root microbial community of naturally farmed rice plants in Japan. A previous study reported that rice fields managed with organic farming practices have a distinct bacterial community composition compared with that of conventionally farmed fields (Suzuki et al, 2019). The root microbial abundance was significantly higher in organically managed crops than in conventionally managed crops (Lenc et al, 2015), and a higher abundance of nutrition-related bacteria was observed (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 90%